Migration and Domestic Space Ethnographies of Home in the Making - Boccagni, Paolo; Bonfanti, Sara (IMISCOE Research Series,, 2023)
This open access book provides insight into the domestic space of people with an immigrant or refugee background. It selects and compares a whole spectrum of dwelling conditions with ethnographic material covering a variety of national backgrounds - Latin America, North and West Africa, Eastern Europe, South Asia - and an equally broad range of housing, household and legal arrangements. It provides a fine-grained understanding of migrants' lived experience of their domestic space and shows the critical significance of the lived space of a house as a microcosm of societal constellations of identities, values and inequalities. The book enhances the connection between migration studies and research into housing, social reproduction, domesticity and material culture and provides an interesting read to scholars in migration studies, policy makers and practitioners with a remit in local housing and integration policies.